2004
DOI: 10.1017/s0959270905000249
|View full text |Cite
|
Sign up to set email alerts
|

Fruit preferences of Malabar Pied Hornbill Anthracoceros coronatus in Western Ghats, India

Abstract: Food habits of Malabar Pied Hornbill Anthracoceros coronatus were studied from December 2000 to December 2001, in the Athikadavu valley, Western Ghats, India. A total of 147 individuals belonging to 18 fleshy-fruited tree species were monitored fortnightly. Thirteen fruit species, including five figs and eight non-figs, were recorded in the birds' diet. The overall number of tree species in fruit and fruiting individuals increased with the onset of summer, the Malabar Pied Hornbill's breeding season. The peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The nesting trees of the MPH were observed at a lower altitude (< 450 m) in riverine habitats of the Pillur valley. Reddy et al (1990) and Balasubramanian et al (2004) stated that the importance of riverine habitats for the conservation of the MPH has been clearly underlined over the years. Mudappa & Raman (2009) recorded the MPH most recurrently at lower altitude (< 600 m) in moist deciduous and riverine areas on the Western Ghats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The nesting trees of the MPH were observed at a lower altitude (< 450 m) in riverine habitats of the Pillur valley. Reddy et al (1990) and Balasubramanian et al (2004) stated that the importance of riverine habitats for the conservation of the MPH has been clearly underlined over the years. Mudappa & Raman (2009) recorded the MPH most recurrently at lower altitude (< 600 m) in moist deciduous and riverine areas on the Western Ghats.…”
Section: Discussionmentioning
confidence: 99%
“…Mudappa & Raman (2009) recorded the MPH most recurrently at lower altitude (< 600 m) in moist deciduous and riverine areas on the Western Ghats. Balasubramanian et al (2004) observed that the distribution and variation in a number of the MPH in the Athikadavu valley region were strongly governed by the availability of fruit trees, their fruiting season and the availability of suitable roosting habitat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations